1998
DOI: 10.1177/002215549804600503
|View full text |Cite
|
Sign up to set email alerts
|

Putative Preneoplastic Changes Identified by Enzyme Histochemical and Immunohistochemical Techniques

Abstract: SUMMARY Microscopic evaluation of whole-mount colons stained with methylene blue and ր or hexosaminidase has identified putative preneoplastic lesions in the colons of rodents treated with carcinogen and in the grossly normal colons of humans. Enzyme histochemistry with glycol methacrylate sections has permitted the identification of putative premalignant lesions in rodent livers, human and rodent colons, and human prostates. Immunohistochemistry with paraffin-embedded tissues has been used to identify and cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…These lesions were first described in the colon of rodents treated with colon-specific genotoxic or non-genotoxic carcinogens and later observed at a high incidence in the colon of patients with sporadic and inherited colon cancer [13][14][15][16]. Biochemical, genetic, and morphological studies have shown that ACF and colon tumors share similar alterations, further supporting the hypothesis that the ACF are precursors of colorectal cancer [17][18][19]. A number of natural compounds that inhibit ACF development have been proved to prevent colon cancer in rodents [20,21].…”
Section: Introductionmentioning
confidence: 82%
“…These lesions were first described in the colon of rodents treated with colon-specific genotoxic or non-genotoxic carcinogens and later observed at a high incidence in the colon of patients with sporadic and inherited colon cancer [13][14][15][16]. Biochemical, genetic, and morphological studies have shown that ACF and colon tumors share similar alterations, further supporting the hypothesis that the ACF are precursors of colorectal cancer [17][18][19]. A number of natural compounds that inhibit ACF development have been proved to prevent colon cancer in rodents [20,21].…”
Section: Introductionmentioning
confidence: 82%
“…A study by Pretlow et al (49) showed that APC mutations are involved in the initiation of aberrant crypt foci, which are precursors to adenoma and colon adenocarcinoma. Goblet cells were already absent from aberrant crypt foci (50). Together, it is possible that the loss of Hath1 expression in aberrant crypt foci may represent an early event in tumorigenesis.…”
Section: Discussionmentioning
confidence: 98%
“…Consistent with our findings, a recent microarray study examining the gene expression profile of Wnt signaling inhibition in LS174T colon cancer cells revealed an increase in MUC2 expression 40. Interestingly, Pretlow and Pretlow41 show that goblet cells are already absent from aberrant crypt foci (ACF), which are precursors to adenoma and colon adenocarcinoma. Since APC mutation is also involved in the initiation of ACF,41 it is possible that the loss of Hath1 expression in aberrant crypt foci may represent an early event in colon tumorigenesis.…”
Section: Relationship Between Hath1 and Wnt Signaling In Colon Adenocmentioning
confidence: 99%